CITIZEN ATTITUDES TOWARDS MILITARY SERVICE AND ITS INFLUENCE ON THE LABOUR MARKET - Shubitidze, Levan (Social Economics, 2025)
Public attitudes toward military service vary widely across nations and contexts, shaped by cultural values, historical experiences, and contemporary global events. This comprehensive study examines the evolution and implications of Georgia’s hybrid military service model, which combines professional military service with mandatory conscription under the new military code. By analyzing extensive survey data, government reports, and real-time recruitment statistics spanning 2008-2023, this research illuminates the multifaceted relationship between citizens’ perceptions of military service and subsequent labor market outcomes across diverse demographic groups in Georgia and the broader Caucasus region. The mixed military service system in Georgia represents a strategic approach to addressing defense workforce challenges by providing a stable pipeline of personnel through conscription while simultaneously maintaining professional positions that offer competitive salaries. This dual structure aims to ensure adequate staffing levels while creating opportunities for those seeking long-term military careers. Our analysis reveals significant variation in how military service experiences translate to civilian employment prospects, wage premiums, and sectoral mobility patterns based on factors including service type, duration, rank, and specialized training received. Against the backdrop of regional instability and Georgia’s unique geopolitical position, this study explores how recent conflicts ‒ including Russia’s 2008 invasion of Georgia, ongoing tensions in occupied territories, and broader regional security dynamics—have fundamentally reshaped popular perceptions of military service in the Georgian Defense Forces. The research methodology combines quantitative analysis of longitudinal survey data with qualitative insights from interviews with military personnel, defense policymakers, and labor economists to provide a holistic understanding of these complex relationships. The study focuses on three interconnected objectives: (1) analyzing public opinion trends regarding military service across different demographic segments, socioeconomic backgrounds, and geographic regions within Georgia; (2) assessing the implications of these attitudes for recruitment strategies, retention rates, and overall military preparedness; and (3) evaluating how military service experiences influence subsequent civilian labor market trajectories, including employment rates, sector-specific placement patterns, wage differentials, and career advancement opportunities. Our findings suggest that military service, particularly in professional capacities, continues to serve as an important pathway for social mobility and skills development for many Georgians, though perceptions vary significantly along urban-rural, educational, and gender lines. The research reveals complex trade-offs in Georgia’s hybrid model, highlighting how mandatory service affects educational trajectories and early career development, while professional service offers specialized training that can translate to valuable civilian sector credentials. Policy recommendations address how defense planners might optimize recruitment messaging, service conditions, and transition support to maximize both national security objectives and positive labor market outcomes for service members. This research contributes to the growing literature on military sociology, labor economics, and defense policy in post-Soviet states, offering insights relevant not only to Georgia but to other nations navigating similar security challenges and workforce development considerations in their defense sectors.